Advective transport of diazotrophs and importance of their nitrogen fixation on new and primary production in the western Pacific warm pool. (25th November 2012) - Shiozaki, Takuhei; Kodama, Taketoshi; Kitajima, Satoshi; Sato, Mitsuhide; Furuya, Ken
Abstract : The western Pacific warm pool (WPWP) is a region of low nutrient and chlorophyll concentrations in which new production is generally considered to be supported by upward fluxes of nitrate from the deep water. A 19 d observation of nitrogen (N2 ) fixation activity and diazotroph abundance along with primary production and nitrate assimilation rate was made at a fixed station in the WPWP. N2 fixation activities accounted for less than half the nitrate assimilation in the first 9 d, then rapidly increased in association with southward current inflow after day 10 and exceeded the nitrate assimilation rate on day 13. During days 11 to 15, soluble reactive phosphorus (SRP) at the surface (39 ± 15 nmol L −1 ) was significantly decreased compared with that in the first 10 d (61 ± 5 nmol L −1 ), and nano‐sized diazotrophs became abundant. Then SRP at the surface further decreased to 20 ± 5 nmol L −1 after day 17, and Trichodesmium and Richelia intracellularis increased concomitant with the reduction of nano‐sized diazotrophs abundance. Both chlorophyll a and primary production increased after day 10, while nitrate assimilation did not increase. Primary production was not correlated with nitrate assimilation but was significantly correlated with N2 fixation, indicating that N2 fixation‐derived nitrogen was the primary source supporting primary production. Time‐series revealed that advective transport of diazotrophs played a critical role in stimulating new and primary production and changed the nutrient inventory.